2004
DOI: 10.1124/jpet.104.069856
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Induced Relaxation of Anococcygeus Smooth Muscle via Desensitization of AT1Receptor, and Activation of AT2Receptor Associated with Nitric-Oxide Synthase Pathway

Abstract: We evaluated the role of receptor desensitization, activation of AT 2 receptors, and enzymatic degradation of angiotensin II (Ang II) by amino/neutral endopeptidases in rat anococcygeus smooth muscle (ASM) relaxation. Ang II (0.3 nM to 10 M) produced contractions (E max ϭ 21.50 Ϯ 5.73%) followed by passive relaxations (E max reduced to 9.08 Ϯ 2.55%). Contractions were inhibited (E max ϭ 13.67 Ϯ 2.03%) by losartan (0.1 M;,7-tetrahydro-1H-imidazo(4,5-c)pyridine-6-carboxylic acid] (0.1 M; AT 2 antagonist). Conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Male Sprague-Dawley rats (300 -350 g) were euthanized by decapitation, and IAS and RSM smooth muscle strips were prepared as described before (10,11). Briefly, using sharp dissection, the IAS and RSM strips exclusively from the circular smooth muscle layer of the muscularis propria (ϳ0.5 mm ϫ 7 mm) were prepared in the oxygenated KrebsЈ physiological solution (KPS).…”
Section: Methodsmentioning
confidence: 99%
“…Male Sprague-Dawley rats (300 -350 g) were euthanized by decapitation, and IAS and RSM smooth muscle strips were prepared as described before (10,11). Briefly, using sharp dissection, the IAS and RSM strips exclusively from the circular smooth muscle layer of the muscularis propria (ϳ0.5 mm ϫ 7 mm) were prepared in the oxygenated KrebsЈ physiological solution (KPS).…”
Section: Methodsmentioning
confidence: 99%
“…Ang II-elicited AT 1 receptor-mediated contractions were counteracted by an AT 2 receptor-mediated active relaxant response sensitive to the neurotoxin TTX. 41 It may be that AT 2 receptors on enteric nerves are operational only in pre-contracted musculature or musculature with a high basal tone like sphincter musculature. In an elegant follow-up study on rat internal anal sphincter, de Godoy and Rattan demonstrated that internalisation of AT 1 receptors and externalisation of AT 2 receptors may be responsible for the activation of the AT 2 receptors, which leads to the relaxation at higher concentrations of Ang II.…”
Section: Gi Wall Musculaturementioning
confidence: 99%
“…According to de Godoy et al (2004), the ANG II-induced relaxation of rat anococcygeus smooth muscle 58 seems to be mediated by stimulation of AT 2 receptors and activation of the nNOS/soluble guanylyl cyclase pathway. Fukuda et al (2005) suggested that AT 2 receptors located in smooth muscle of rat aortic rings may mediate vasorelaxation via stimulation of the NO-cyclic GMP pathway, vasodilator cyclooxygenase products, and voltage-dependent and Ca 2ϩ -activated large-conductance K ϩ channels.…”
Section: Angiotensin-induced Endothelium-derived Relaxing Factomentioning
confidence: 99%